2018
DOI: 10.3389/fpsyg.2018.01543
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fluency With Language Proficiency, Working Memory, and Directionality in Simultaneous Interpreting

Abstract: Simultaneous interpreting (SI) is a complex bilingual verbal activity that poses great challenges for working memory (WM) and language proficiency. Fluency is one of the crucial indicators in evaluating SI quality, the violation of which is characterized by disfluency indicators such as interruptions, hesitations, repetitions, corrections, and blanks. To uncover factors underlying fluency in SI, 22 interpreting students performed a battery of tasks to test their language proficiency and WM. Two SI tasks, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 45 publications
1
32
1
Order By: Relevance
“…To avoid the possible cognitive resources saturation, the information retained in the focus of attention for processing should be kept as small in amount as possible. Hence, SI interpreters usually produce the output without much altering the sequence of source text elements, avoiding the increased pressure which would have been entailed by reordering the parts (Hatim and Mason, 2002; Lin et al, 2018). In this way, the chunks of information can be relieved from the focus of attention immediately after they are formulated in the target language (Liang et al, 2017; Mizuno, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the possible cognitive resources saturation, the information retained in the focus of attention for processing should be kept as small in amount as possible. Hence, SI interpreters usually produce the output without much altering the sequence of source text elements, avoiding the increased pressure which would have been entailed by reordering the parts (Hatim and Mason, 2002; Lin et al, 2018). In this way, the chunks of information can be relieved from the focus of attention immediately after they are formulated in the target language (Liang et al, 2017; Mizuno, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous interpretation requires extensive linguistic knowledge and cognitive resources, as interpreters must concurrently comprehend one language while producing another. It is therefore perhaps unsurprising that working memory has been identified as a major predictor of performance among this specialized population (Christoffels et al 2003;Lin et al 2018;Macnamara and Conway 2016;Tzou et al 2012). Other factors including L2 proficiency (Tzou et al 2012), translation expertise (Garcia et al 2014), and the ability to inhibit distractors (Timarová et al 2014) have also been linked to interpreting performance.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this is that working memory capacity is thought to be a predictor at comparatively lower levels of skill acquisition and plays an essential role when the skill is still not yet automatic ( Timarová et al, 2015 ). Studies relating cognitive abilities directly to fluency in interpreting have been scarce, but working memory capacity was found to predict SI fluency in trainee interpreters’ SI fluency performance in the study of Lin et al (2018) , which indicated the critical role of working memory capacity as compared with language skills in SI fluency.…”
Section: Introductionmentioning
confidence: 91%
“…It would also verify the effectiveness of including working memory capacity as a construct of cognitive fluency in interpreting research. In the field of interpreting studies, cognitive factors have been found important for interpreting performance ( Christoffels et al, 2003 ; Injoque-Ricle et al, 2015 ; Macnamara and Conway, 2016 ; Lin et al, 2018 ). Previous interpreting studies on the relationship of cognitive fluency related aspects and interpreting performance, in particular, lexical access and retrieval, cognitive control, and working memory capacity, were introduced in the following.…”
Section: Introductionmentioning
confidence: 99%